Performance Evaluation of the MBT STAR®-Carba IVD Assay for the Detection of Carbapenemases With MALDI-TOF MS - Anantharajah, Ahalieyah; Tossens, Bastien; Olive, Nathalie; Kabamba-Mukadi, Benoit; Rodriguez-Villalobos, Hector; Verroken, Alexia (Frontiers in Microbiology, 2019)
Objectives: The increasing rate of carbapenem resistance in Gram-negative bacteria is a major public health problem and rapid detection is essential for infection management. We evaluated the performances of the MBT STAR®-Carba IVD assay (Bruker Daltonics) to detect carbapenemase-producing organisms (CPO) from bacterial colonies and directly from positive blood culture bottles with MALDI-TOF MS. Methods: We analyzed 130 strains with a reduced susceptibility to at least one carbapenem including 109 CPO (6 KPC, 27 NDM, 21 VIM, 1 IMP, 41 OXA-48-like, 8 OXA-23, 2 OXA-24/-40 and 2 OXA-58) and 21 non-CPO. The assay on colonies was performed with all 130 strains while the assay on spiked blood cultures was performed with 45 strains. Samples were prepared with the MBT STAR®-CARBA IVD kit and imipenem hydrolysis by the potential carbapenemase was analysed with the MBT STAR®-BL module (Bruker Daltonics) on MALDI-TOF MS. Results: Performed on colonies, the assay detected all carbapenemase-producing Enterobacteriaceae (n=78), Pseudomonas spp. (n=19) and Acinetobacter spp. (n=12). All 21 tested non-CPO remained negative resulting in sensitivity and specificity of 100%. Performed on positive blood cultures, the assay detected all carbapenemase-producing Enterobacteriaceae (n=23) and Pseudomonas spp. (n=4) but missed 9/12 carbapenemase-producing Acinetobacter spp. However, a prolonged imipenem-incubation time of the strain pellet improved carbapenemase detection. Non-CPO from positive blood culture bottles remained negative (n=5) with the assay with the exception of one K. pneumoniae isolate. Conclusions: The MBT STAR®-Carba IVD assay is a highly reliable method for the detection of carbapenemase activity in Gram-negative bacteria. However, time-consuming sample preparation steps and reagent costs need to be considered before implementation in a routine clinical microbiology laboratory.